Psychometric properties of the Moroccan dialect versions of the Perceived Stress Scale and the Center for Epidemiologic Studies Depression Scale among Moroccan university students - Younes RAMI; Hicham KHABBACHE; Jamal AMRAOUI; Driss AIT ALI; Zakaria ABIDLI; Abdulmohsen MOHAMMED ABDULLAH ALKHULAYFI; Mahmood BAHRAMIZADEH; Hassan LAABOUB; Amelia RIZZO; Bouabid BADAOUI; Şeyhmus AKSOY; Lukasz SZARPAK; et al. (Journal of Health and Social Sciences)
Introduction: This study investigates the psychometric properties of the Moroccan dialect versions of the Perceived Stress Scale (PSS-10) and the Center for Epidemiologic Studies Depression Scale (CES-D-10) in a sample of Moroccan university students. The objective is to evaluate the reliability and validity of these scales for assessing perceived stress and depressive symptoms among this population. Methods: We conducted a cross-sectional survey of 204 Moroccan university students. Stress and depression levels were measured using the PSS-10 and the CES-D-10. The psychometric properties of the PSS-10 and CES-D-10 were assessed based on internal consistency, internal coherence, and confirmatory factor analyses. Results: The study demonstrated an adequate fit for the PSS-10 (χ²(25) = 44.591, CFI = 0.989, TLI = 0.985, SRMR = 0.058) and CES-D-10 (χ²(25) = 62.993, CFI = 0.955, TLI = 0.942, SRMR = 0.046) scales. Additionally, the PSS-10 and CES-D10 exhibited significant correlation (r = .75, p < .01) further reinforcing their convergent validity. Discussion: Consistent with previous research, the internal consistency, internal coherence, and confirmatory factor analyses were satisfactory for both the PSS-10 and CES-D-10 in the Moroccan university context. These findings suggest that the PSS-10 and CES-D10 are robust tools for assessing perceived stress and depression, making them valuable instruments for researchers and clinicians in the field of mental health.